Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{(x - a)^2 + (y - b)^2 = R^2}[/tex]
[tex]\mathsf{x^2 + y^2 + 8x + 4y - 5 = 0}[/tex]
[tex]\mathsf{x^2 + 8x + y^2 + 4y - 5 = 0}[/tex]
[tex]\mathsf{x^2 + 8x + 16 - 16 + y^2 + 4y + 4 - 4 - 5 = 0}[/tex]
[tex]\mathsf{(x^2 + 8x + 16) - 16 + (y^2 + 4y + 4) - 4 - 5 = 0}[/tex]
[tex]\mathsf{(x + 4)^2 - 16 + (y + 2)^2 - 4 - 5 = 0}[/tex]
[tex]\mathsf{(x + 4)^2 + (y + 2)^2 = 25}[/tex]
[tex]\mathsf{R^2 = 25}[/tex]
[tex]\mathsf{R = \sqrt{25}}[/tex]
[tex]\mathsf{R = 5}[/tex]
[tex]\mathsf{D = 2R}[/tex]
[tex]\mathsf{D = 2(5)}[/tex]
[tex]\boxed{\boxed{\mathsf{D = 10}}}[/tex]